Intervensi Guru dalam Diskusi Kelompok untuk Mengurangi Muatan Kognitif Intrinsik - Nufe Auliya’ Bernadine; I Nengah Parta; Dahliatul Hasanah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
Intrinsic Cognitive Load (ICL) is a cognitive load inherent in the material and has a positive impact on learning. However, working memory as an active tool that processes cognitive load has limited capacity, and ICL cannot be completely eliminated. Group learning is one of the learning methods that can help manage ICL. Mathematics is one of the subjects with high ICL, including the Pythagorean theorem. This study aims to analyze the forms of teacher intervention during group discussions that support students in managing ICL while constructing the Pythagorean Theorem. The data source of this study consisted of 14 eighth-grade students divided into four groups. The results showed that prerequisite activation, validation, scaffolding, and abstraction in teacher interventions helped eliminate ICL.